2010
DOI: 10.4103/0973-1296.62899
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the toxic effect of star fruit on serum biochemical parameters in rats

Abstract: The objective of the present study was to evaluate the toxic effect of Averrhoa carambola (star fruit) juice at different storage conditions in Sprague Dawley (SD) rats. Twenty female rats weighing 180 ± 20 g were randomly assigned into four groups with five rats per group (n = 5). First group served as the control group, fed with distilled water (vehicle). Second, third and fourth groups were orally treated with juice of A. carambola stored for 0, 1 and 3 h respectively for 14 days. Cage-side observations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Several serum enzymes are used as indicators or markers for hepatocellular injuries, such as ALT and AST. 36 Injured on liver release those cytosolic enzymes (ie, ALT and AST) in the blood cause elevation of their concentration in blood. 37 , 38 From liver-function tests, we found that serum ALT and AST were significantly increased in rats treated with Mn.…”
Section: Discussionmentioning
confidence: 99%
“…Several serum enzymes are used as indicators or markers for hepatocellular injuries, such as ALT and AST. 36 Injured on liver release those cytosolic enzymes (ie, ALT and AST) in the blood cause elevation of their concentration in blood. 37 , 38 From liver-function tests, we found that serum ALT and AST were significantly increased in rats treated with Mn.…”
Section: Discussionmentioning
confidence: 99%
“…Serum biochemistry is important for monitoring liver function in toxicology studies [ 16 – 18 ]. The highest doses of MHEE caused an increase of GLU, TP, and ALB levels in female rats.…”
Section: Discussionmentioning
confidence: 99%
“…ALP is present in the cells lining the hepatic biliary ducts, while ALT exists in the cytoplasm of hepatocytes. 32 Increase in the plasma ALT concentration indicates altered hepatocellular membrane permeability resulting in the leakage of the enzyme into the bloodstream, 33 perhaps due to the presence of the nanoparticles. This could eventually progress to hepatocellular damage/necrosis, hepatocyte proliferation or hepatocellular degeneration.…”
Section: Resultsmentioning
confidence: 99%